2008
DOI: 10.1200/jco.2007.14.1366
|View full text |Cite
|
Sign up to set email alerts
|

Graft-Versus-Lymphoma Effect for Aggressive T-Cell Lymphomas in Adults: A Study by the Société Française de Greffe de Moëlle et de Thérapie Cellulaire

Abstract: We conclude that alloSCT is a potentially efficient therapy for NK/T lymphomas and is worth further investigation through prospective clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
205
2
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(225 citation statements)
references
References 25 publications
12
205
2
6
Order By: Relevance
“…15,35,36 Similarly, Corradini et al 35 reported 17 patients with relapsed or refractory disease who underwent a reduced intensity allogeneic procedure. The authors found an impressive OS of 80% and PFS of 60% at 3 years.…”
Section: Allo-hsct For Ptclmentioning
confidence: 99%
See 1 more Smart Citation
“…15,35,36 Similarly, Corradini et al 35 reported 17 patients with relapsed or refractory disease who underwent a reduced intensity allogeneic procedure. The authors found an impressive OS of 80% and PFS of 60% at 3 years.…”
Section: Allo-hsct For Ptclmentioning
confidence: 99%
“…Recently, Le Gouill et al 36 and other French investigators have reported their retrospective experience in 77 patients with several subtypes of PTCL who underwent Allo-HSCT. In this series, most patients underwent a full myeloablative procedure and again the results were encouraging with a 57% 5-year OS and a corresponding 53% EFS.…”
Section: Allo-hsct For Ptclmentioning
confidence: 99%
“…[1][2][3] RIC regimens also have been investigated in patients with aggressive lymphomas: Most of those studies included various B-cell and T-cell histotypes, and the estimated 3-year PFS rates have been 15% to 20% in patients with chemoresistant disease and 45% to 55% in patients with chemosensitive disease. [4][5][6][7] Chemosensitivity is 1 of the most important prognostic factors affecting final outcomes in patients who receive myeloablative conditioning, and is also important for patients who receive RIC regimens. We recently demonstrated better overall survival (OS) and PFS in patients with lymphoma who underwent an allograft in complete remission compared with the survival of patients who underwent transplantation in partial remission or with refractory disease.…”
mentioning
confidence: 99%
“…2 Allogenic SCT (allo-SCT) is increasingly used as an alternative strategy, based on a potent graft-versus-lymphoma effect (GvL). However, data from retrospective [3][4][5][6][7][8][9][10][11] and prospective non-randomized studies 12 are insufficient to recommend allo-SCT as first-line treatment. The European Bone Marrow Transplantation Society currently considers allo-SCT to be an option for selected patients with chemosensitive disease in first or second complete response (CR), if a sibling or unrelated HLA-matched donor is available (grade 2 recommendations).…”
Section: Introductionmentioning
confidence: 99%
“…Second, in most studies the survival curve stabilized after 12-18 months, suggesting a possible curative effect. 4 Third, chronic GvHD has been linked to a lower risk of relapse. 5 Finally, a negative impact on survival, due to a high relapse rate (70%), has been reported with T-cell-depleted grafts in primitive cutaneous T-cell lymphoma (TCL).…”
Section: Introductionmentioning
confidence: 99%